Respuesta :

The answer is 18

You want to substitute in the values for everything so z = 6 y = 4 and x = 2

So when you substitute it into the equation you get 4(2) + 4^2 -6

When simplified your get 8+16-6

When solved equals 18

Answer:

18

Step-by-step explanation:

We're given an expression and information about the values of the variables in it. The problem says that  x = 2, y = 4, z = 6. Thus, to evaluate the expression, substitute those values for the matching variables within the expression and solve:

[tex]4x+y^2-z\\= 4(2)+(4)^2-(6)\\= 8 + 16 - 6 \\= 24 - 6\\= 18[/tex]

So, the answer is 18.